Immunopathological Changes of Streptococcus pneumoniae Causing Respiratory Infection in Lambs - A Hamzah, Abbas; I Ibrahim, Zainab (The Iraqi Journal of Veterinary Medicine, 2024)
Streptococcus pneumoniae are common bacterial pathogens that can cause a range of diseases in humans and animals. This study attempts to clarify the course and consequences of pneumonia caused by this bacterial infection. A total of 6 male un-weaned lambs aged between 1 to 2 months and weighing 5 to 7 kg were subjected to S. pneumoniae strain ATCC 6303 serotype 3 at ‎2×106 ‎CFU/mL by inhalation to induce pneumonia. Pneumonic clinical signs were ‎monitored daily throughout the study period. The blood samples were collected from all animal groups at day zero before pneumoniae induction and 3, 6, and 14 days post infection for total and differential white blood cell count ‎(WBCs) and tumor necrosis factor-alpha (TNF-α) assessments. Additionally, on days 6 and 14 post-exposure, trachea and lung tissue samples were harvested for macroscopic and microscopic pathological changes evaluation. The results showed that there was a significant increase (P<0.001) in total WBC counts from day 3 post-exposure and maintaining elevated levels on days 6 and 14 compared to day zero. Differential WBC counts showed an early, significant rise in neutrophils, with sustained ‎elevation in lymphocytes and monocytes. TNF-α‎ levels significantly elevated on day 3‎ and gradually declined by day 14‎ post-exposure (P<0.001). On day 6 post-exposure, the gross pathological changes in the lung showed pulmonary edema, and emphysema, with mild to moderate lung congestion and emphysematous changes observed on day 14 post-exposure. Histopathologically, severe erosion and necrosis in the trachea and bronchus epithelium, along with inflammation in adjacent mucosa and submucosa, accompanied by focal inflammatory infiltration and emphysema in the lung by day 6 post-exposure, were observed. By day 14, these changes progressed to marked epithelial vacuolation and necrosis in the trachea, with lung sections revealing perivascular cuffing, peri bronchiolitis, mild bronchiectasis, atelectasis, and alveolar collapse. This study is attempt for a better understanding of S. pneumoniae infection in lamb and contributing to the development of preventive and management strategies in Iraq‎‎‎.